Legal Knowledge and Information Systems : JURIX 2013: The Twenty-Sixth Annual Conference. - Ashley, K. D. (IOS Press, 2013)
In the same way that it has become part of all our lives, computer technology is now integral to the work of the legal profession. The JURIX Foundation has been organizing annual international conferences in the area of computer science and law since 1988, and continues to support cutting-edge research and applications at the interface between law and computer technology.This book contains the 16 full papers and 6 short papers presented at the 26th International Conference on Legal Knowledge and Information Systems (JURIX 2013), held in December 2013 in Bologna, Italy. The papers cover a wide.